Improving Science Learning Outcomes Through Contextual-Based Picture Media for Students With Learning Difficulties in Elementary Schools - Antonius Nuwa Jo; Ishartiwi Ishartiwi; Rendy Roos Handoyo (PT Publikasiku Academic Solution, 2025)
Elementary education plays a crucial role in laying the foundation of students’ knowledge and skills. Science and Social Studies (IPAS) is one of the core subjects that equips students with an understanding of their environment and society. However, students with learning difficulties often face challenges in comprehending abstract concepts presented in IPAS lessons. This study aims to investigate the effectiveness of context-based picture media in improving IPAS learning outcomes among slow learner students in elementary school. This research employed a classroom action research (CAR) design conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through written tests, classroom observations, and interviews with teachers. The intervention focused on using contextual picture media that related directly to students’ daily experiences, such as markets, plants around the school, and community activities. The findings show a significant improvement in students’ learning outcomes. The average score increased from 62.5 in the pre-action stage to 71.3 in the first cycle, and further to 81.7 in the second cycle. Mastery learning also rose from 35% to 65% and ultimately 90%. Moreover, observations revealed higher student participation, stronger motivation, and increased confidence in expressing ideas during learning activities. Teachers also noted that contextual images helped students connect abstract concepts with real-life situations, making lessons more meaningful and interactive. In conclusion, the use of contextual picture media has proven effective in enhancing IPAS learning outcomes for students with learning difficulties. This approach not only improves cognitive achievement but also fosters affective and psychomotor development, making it a practical strategy for inclusive education in elementary schools.